2009
DOI: 10.1177/1721727x0900700303
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Chlamydia Pneumoniae in Northern Greece

Abstract: The prevalence of IgG and IgA antibodies to Chlamydia pneumoniae was evaluated in a group of an apparently healthy population in northern Greece. Serum samples were obtained over a period of one year (June 2006 to May 2007) from 530 individuals (300 males and 230 females, aged from 1 month to 90 years). The sera were tested for specific antibodies to C. pneumoniae by two commercial methods, an ELISA and a micro-IF assay based on the principles of MIF. The prevalence of IgG and IgA antibodies to C. pneumoniae w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…pneumoniae is a widespread cause of infection, with an estimated seroprevalence of over 50% among adults in many countries [35][36][37]. However, the prevalence is relatively low in children under 5 to 10 years old (7-8%), but it sharply increases to 40-55% in those aged 20 and continues to increase gradually, reaching 70-80% in the elderly [38,39].…”
Section: Pneumoniae: a Pathogen Causing More Than Pneumoniaementioning
confidence: 99%
“…pneumoniae is a widespread cause of infection, with an estimated seroprevalence of over 50% among adults in many countries [35][36][37]. However, the prevalence is relatively low in children under 5 to 10 years old (7-8%), but it sharply increases to 40-55% in those aged 20 and continues to increase gradually, reaching 70-80% in the elderly [38,39].…”
Section: Pneumoniae: a Pathogen Causing More Than Pneumoniaementioning
confidence: 99%
“…Serological studies showed that C. pneumoniae is common, with a seroprevalence of over 50% among adults, indicating previous infection [16][17][18][19]. In addition, prevalence is relatively low in children under five to ten years (7-8%), sharply increases by the age of 20 (%40-55), and continues to increase gradually to rise in the elderly to 70-80% [16,20].…”
Section: Chlamydia Pneumoniamentioning
confidence: 99%